The Multifaceted Role of Alpha-Lipoic Acid in Cancer Prevention, Occurrence, and Treatment - Shuai Yan; Jiajie Lu; Bingqing Chen; Liuxia Yuan; Lin Chen; Linglin Ju; Weihua Cai; Jinzhu Wu (MDPI AG, 2024)
Alpha-lipoic acid (ALA) is a naturally occurring compound synthesized by mitochondria and widely distributed in both animal and plant tissues. It primarily influences cellular metabolism and oxidative stress networks through its antioxidant properties and is an important drug for treating metabolic diseases associated with oxidative damage. Nevertheless, research indicates that the mechanism by which ALA affects cancer cells is distinct from that observed in normal cells, exhibiting pro-oxidative properties. Therefore, this review aims to describe the main chemical and biological functions of ALA in the cancer environment, including its mechanisms and effects in tumor prevention and anticancer activity, as well as its role as an adjunctive drug in cancer therapy. We specifically focus on the interactions between ALA and various carcinogenic and anti-carcinogenic pathways and discuss ALA's pro-oxidative capabilities in the unique redox environment of cancer cells. Additionally, we elaborate on ALA's roles in nanomedicine, hypoxia-inducible factors, and cancer stem cell research, proposing hypotheses and potential explanations for currently unresolved issues.